Nutrients density of confectionary products consumed in Peshawar and Mardan Divisions (NWFP) - Khattak, Muhammad Muzaffar Ali Khan; Khan, Alam; Jan, Mohammad (National Agricultural Research Centre (Pakistan), 2003)
Ingredients composition and nutritional evaluation of four types of each of barffies and rasgullas, 5 types of sweets and 11 other miscellaneous products namely amratee, halwa, laddo, somosa, pateesa, perra, namakpara, pakora, masu, abidana and pistaroll, prepared in Peshawar, Charsadda, Nowshera districts (Peshawar Division), Mardan and Swabi districts (Mardan Division) were determined. The average ingredient composition of burffies was 47% sugar, 23% milk and 2% fat, In Choharbar and Kaddo burffies, 16% dates and 28% pumpkin respectively were the additional ingredients. The average ingredient composition of rasgullas was 63% sugar, 2440 milk and 940 fat. In sweets, the average ingredient composition was 33% flour, 30% sugar, 2% milk and 17% fat. Almonium Masala was used in small amount in Rajur and Sada sweets. Flour, sugar, milk, fat, basin, onion, potato, meat, egg and spices were the ingredients for the various miscellaneous products. The average proximate composition of barflies was 8.87% moisture, 6.26% protein, 18.39% fat, 1.69 ash, 1.97% fiber and 63.10% carbohydrate. The average caloric value of barffies was 445 Kcal/100g of barflies. The average chemical composition of rasgullas was 21.20% moisture, 7.74% protein, 28.29% fat, 1.45% ash, 1.64% fiber and 39.66% carbohydrate. The average caloric value of rasgullas was 445 Kcal/100 g of the product. The average proximate composition of sweets was 8.88% moisture, 8.98% protein, 30.21% fat, 1.13% ash, 3.35% fiber and 48.06% carbohydrates. The average caloric value of sweets was 501 Kcal/100 g of the product. The protein contents of amartee, halwa, laddo, somosa, perra, pateesa, namakpara, pakora, masu, abidance and pistaroll were 3.33%, 2.70% 5.43%, 5.25%, 8.90%, 2.63%, 5.76%. 7.91 2.63%, 2.95% and 8.58%, respectively. The fat contents of these products were 18.53%, 20.51%, 31.95%, 31.57%, 2.01%, 23.30%, 28.00%, 23.00%, 31.00%, 21.10 and 18.68% respectively. The carbohydrate contents of these products were 68.33%, 50.34%, 45.12%, 31.84%, 63.13%, 69.02%, 58.66%, 11.08%, 62.53%, 56.47% and 55.26%. respectively. The caloric values of these products were 453, 397, 490, 433, 306, 496, 510, 283, 540, 428 and 424 Kcal/100 g of the products respectively. In general, confectionery products are low in protein and high in fat and sugar. Excessive consumption of confectionery products may cause ill effects in health.